Arsitektur Berbasis Kesehatan Mental : Menciptakan Ruang yang Mendukung Kesehatan Emosional - Farokhatu Ulyana; Adhe Ayala Levandani (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
Mental health is an important aspect of an individual's well-being, which is influenced by various factors, including the physical environment. Data from the Indonesian Ministry of Health shows an increasing prevalence of mental disorders, with depression and anxiety being the predominant disorders across different age groups. Architecture has a significant influence on psychological well-being, where good space design can reduce stress, increase social interaction, and create a sense of security. Natural lighting, green open spaces, and layouts that support social interaction can help reduce symptoms of anxiety and depression. From an Islamic perspective, mental health is also considered an integral part of well-being, with the concept of maslahah encouraging the creation of environments that support physical and mental well-being, including through space design that takes into account spiritual aspects. Based on recent data, mental disorders, especially depression and anxiety, are on the rise, with significant impacts on society, both in terms of individuals, families, and national productivity. This research aims to examine the implementation of architectural designs that support the healing of mental disorders as well as the relationship between architecture and spirituality according to Islamic views. This research is expected to provide insights in designing spaces that not only support the psychological healing process, but also create an environment that is aligned with spiritual values that can strengthen the mental well-being of individuals.